Need for Conservation and Propagation of Alpine and Sub-alpine Medicinal Plants of North-west Himalayas - Joshi, D. N.; Rawat, G. S. (Indian Forester, 1997)
The alpine and sub-alpine areas of North-West Himalayas provides a matchless wealth of highly priced medicinal, aromatic plants and are known as a natural reservoir of these herbs. In alpine pasture and meadows (bugyals) due to continuous loss of forest land, uncontrolled grazing and irregular exploitation of medicinal helrbs by commercial enterprises have resulted in depletion of valuable medicinal plants used since ancient times. There are many medicinal plants which have become rare in several tracts while a few others have fallen in the list of endangered species. Therefore it has been felt that there is an urgent need for conservation, ex-situ and in-situ cultivation of these valuable and threatened species by establishing high altitude nurseries in their natural habitat, so that regular supply to pharmaceutical industries and users could be maintained and above all this valuable flora of the alpine/sub-alpine areas of North-West Himalayas could be conserved.